Effectiveness of self-testing kits availability on improving HIV testing frequency for chinese men who have sex with men and their sexual partners: a protocol for a multicenter randomised controlled trial. Issue 12 (14th December 2018) - Zhang, Ci; Li, Xianhong; Koniak-Griffin, Deborah; Goldsamt, Lloyd A.; Zhou, Jing
Abstract : Introduction: HIV epidemic is increasing among men who have sex with men (MSM) in China, yet HIV testing uptake remains low. As an emerging approach, HIV self-testing (HIVST) has the potential to promote HIV testing coverage and frequency in this population. However, evidence of the effectiveness on implementation of HIVST among Chinese MSM and their sexual partners is scarce. Methods and analysis: The randomised controlled trial will be performed in Changsha, Changde, Shaoyang and Yiyang, Hunan province, China, recruiting 184 recent testers (men who had at least one HIV test within the past 2 years) and 26 non-recent testers (men who did not have HIV tests within 2 years or never had an HIV test). Eligible men will be randomly divided 1:1 into two groups: intervention (with free HIVST kits plus site-based HIV testing services) and control (site-based HIV testing services only). Participants in the intervention group will be provided with two free finger-prick-based HIVST kits, and can apply for two to four kits every 3 months for 1 year. Participants in both groups will complete questionnaires via WeChat at five separate times: baseline, third, sixth, ninth and twelfth month. The primary outcome is the mean number of HIV tests for MSM over the 12-month study period. The secondary outcome is the mean number of HIV tests for sexual partners of MSM over the 12-month study period. The tertiary outcomes are the self-reported proportion of consistent condom usage for anal sex, and the numbers of sexual partners during the 12-month study period. Ethics and dissemination: The study has been approved by the Institutional Review Board of Behavioural and Nursing Research in Xiangya School of Nursing of Central South University, China (2018002). Study results will be disseminated through conferences and academic journals. Trial registration number: ChiCTR1800015584; Pre-results.